Functional equivalence and the new Dutch translation project - K. F. de Blois; T. Mewe (Acta Theologica)
In this article De Blois and Mewe demonstrate how functional-equivalent principles had been originally defined with regard to the Netherlands Bible Society’s Nieuwe Bijbelvertaling (New Bible Translation) and had to be redefined in light of the need for a better theoretical model. The model, outlined in the article, also served as a handle to avoid ambiguity and inconsistency in the way principles were interpreted and/or implemented, and created a framework for responding to needs expressed by the target audience.